MEKANISME KOORDINASI PEMBERDAYAAN PRODUSEN GENTENG MELALUI KEBIJAKAN GENTENGISASI NASIONAL DI KABUPATEN MAJALENGKA - Heru Sulistiyo; Abdurohim Abdurohim; Rifa'i M. (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2026)
ABSTRACT  The "national roof tile" policy, as part of the National Movement to create an ASRI (Safe, Healthy, Clean, and Beautiful) environment in Indonesia, presents a unique challenge for local governments with roof tile producers. This policy can empower roof tile entrepreneurs and have a multiplier effect during a sluggish industrial sector. Roof tile production issues relate to meeting market demand, product standardization, and aesthetics, all of which can be addressed with government support. The purpose of this study is to analyze the government's coordination mechanisms in response to this national policy. This study employed a qualitative, descriptive-analytical approach, utilizing both primary and secondary data. Primary data was obtained directly in the field through observation and interviews, while secondary data was obtained through documentation and other pre-existing sources in the form of articles or digital data available online. The results indicate that the collective coordination scheme through institutional mechanisms is considered effective because it can meet the expectations of roof tile craftsmen, indicated by increased production volumes, while also avoiding fierce competition between companies. In addition, challenges related to producers' ability to meet demand, product quality standardization, and the aesthetic aspects of roof tile designs to meet consumer needs can be addressed collaboratively.